2016
DOI: 10.4149/km_2014_1_43
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on laser brazing of austenitic and martensitic stainless steels with silver-based filler metal

Abstract: In the present study, laser brazing of austenitic stainless steel (type 321) and martensitic stainless steel (type 410) have been performed using 400 W pulsed Nd:YAG laser with silverbased filler metal. The microstructure was investigated using Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDS). The laser brazed joints consist of α-Ag solid solution, α-Cu solid solution surrounded by the α-Ag solid solution and eutectic structure. Filler metal shows better spreading on 321 stainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Laser brazing is a new technique successfully used in brazing of various materials. 1012 Its major advantage over other brazing procedures is that the joint area can be heated precisely without heating the entire workpiece to the liquidus of the brazing filler metal. This limits the flow of the braze filler metal to the area heated by the laser beam and precludes any flow due to capillary action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser brazing is a new technique successfully used in brazing of various materials. 1012 Its major advantage over other brazing procedures is that the joint area can be heated precisely without heating the entire workpiece to the liquidus of the brazing filler metal. This limits the flow of the braze filler metal to the area heated by the laser beam and precludes any flow due to capillary action.…”
Section: Introductionmentioning
confidence: 99%
“…Khorram et al 12 investigated laser brazing of austenitic stainless steel and martensitic stainless steel with BAg-8 filler metal. They concluded that the sound joints can be obtained by BAg-8 filler metal.…”
Section: Introductionmentioning
confidence: 99%